Dor persistente pós-operatória em cirurgias cardíacas e fatores de risco associados: estudo prospectivo observacional - Stüker, Nonie Candace (2020)
Introduction: Persistent postoperative pain (DPPO) is a consequence of the surgical procedure and has aroused great interest in health professionals due to the losses and difficulties in treatment and its high cost. Among surgical procedures, cardiac surgery is especially important because it has a high incidence and generates an extremely high preoperative anxiety level. The mechanisms of postoperative pain persistence are complex and not fully understood. Objective: The present study aims to assess the incidence of DPPO in the cardiac surgery service of HUSM (Hospital Universitário de Santa Maria-RS), as well as the identification of risk factors for development. Methodology: A prospective observational study was performed, using a collection instrument, in patients undergoing cardiac surgery with sternotomy at the HUSM during 12 months with the expectation of capturing 103 patients, according to inclusion and exclusion factors. In order to highlight the influence of psychosocial factors on acute pain, anxiety was assessed using the HADS A scale, depression, in turn, was assessed using the HADS D scale and negative beliefs and exaggerated responses using the catastrophizing scale. Results: This study showed a 57% incidence of DPPO in patients undergoing cardiac surgery with sternotomy, after 3 months. Significant correlation was identified between anxiety profile (p=0.003), pain at 48h (p=0.022), previous psychic disorders (p=0.044), previous use of medications antidepressants (p=0.027) and the development of DPPO. The most significant variables for DPPO logistic regression in relation to the scales, from the determination of the adjusted OR, Were HADS A (p=0.015) presenting 10.93 times more chance of presenting chronic pain, Pain at 48 hours (p=0.009) with 2.79 more chance of progressing to DPPO and with 5.04 greater chance of presenting DPPO due to the use of antidepressants (p=0.041).Conclusion: Based on the results obtained, it is possible to associate risk factors such as anxiety and catastrophization to the development of DPPO, compared to the population studied. It is worth mentioning that the correct identification and treatment of AD and subacute are important factors to be evaluated during the anamnesis of patients who underwent cardiac surgery with sternotomy, in order to reduce the progression of the condition to DPPO, as pain in 48 hours after the procedure is also showed a risk factor. In addition, the fact of using antidepressants brings greater chances of developing DPPO, according to this study.